Synthesis, structure and dynamics of methoxynaphthalene-substituted phospha-ruthenocenes and -ferrocenes. - Carmichael, D; Ricard, L; Seeboth, N; Brown, J; Claridge, T; Odell, B (2005)
The syntheses of potassium 2-(2'-methoxynaphth-1'-yl)-3,4-dimethyl-5-phenylphospholide 4 and eta5-pentamethylcyclopentadienyl(eta5-2-(2-methoxynaphth-1-yl)-3,4-dimethyl-5-phenylphospholyl)-ruthenium(II)5 and -iron(II)6 are described. The barrier to rotation of the naphthyl group (79 kJ mol-1 and 72 kJ mol-1 in CD2Cl2 respectively) characterises 5 and 6 as potential tropos type ligands. Coordination of 5 to [PtCl2(PEt3)] gives two cis and two trans complexes [PtCl2(PEt3)5] wherein rotation about the phospholyl-naphthyl vector is slow.